Resistivity imaging and uncertainty assessment of volcanic covered sedimentary basins of India derived from a new strategy - Jit Varish Tiwari; Kuldeep Sarkar; Upendra K. Singh (Applied Computing and Geosciences)
In basalt-covered areas like Saurashtra, India, the Deccan Traps are a significant part of the Indian lithosphere with notable geophysical anomalies and tectono-thermal history dating back to the Mesozoic. Magnetotellurics (MT) is commonly used to image subtrappean Tertiary and Quaternary strata in these regions. We assessed the Improved Wolf Optimization (IWOA) strategy, inspired by whale hunting behavior, to enhance the electrical resistivity structure in basalt-covered regions without relying on seismic and borehole data. Initially tested on theoretical/synthetic MT datasets representing geological scenarios, IWOA was then applied to field data from hydrocarbon potential basins: (i) trap-covered areas, yielding reliable subsurface models with MT alone, and (ii) traps overlain by conductive Tertiary sediments. Instead of selecting the global model with the lowest error, we used Bayesian posterior probability density function (PDF) to reconstruct models. This approach considers models with PDF values above 68.27 % confidence interval, constructing an average model from these models with lesser uncertainty. Our analysis revealed a thick subtrappean Tertiary sedimentary layer over volcanic cover in the Cambay basin. The method also identified two layers: a highly conductive layer likely alluvium and a major resistive layer probably due to volcanic deposits. These findings align with geological stratigraphy and drill samples, demonstrating that IWOA provides a reliable and superior subsurface model.